Modelling of multi-component kerosene and surrogate fuel droplet heating and evaporation characteristics: A comparative analysis. (1st June 2020) - Poulton, L.; Rybdylova, O.; Zubrilin, I.A.; Matveev, S.G.; Gurakov, N.I.; Al Qubeissi, M.; Al-Esawi, N.; Khan, T.; Gun'ko, V.M.; Sazhin, S.S.
Highlights: Application of the Discrete Component Model to kerosene droplets. Modelling of heating and evaporation of suspended kerosene droplets. Effects of support and natural convection on droplet heating/evaporation. Validation of the predictions of the model against experimental data. Selection of kerosene surrogates using droplet heating/evaporation characteristics. Abstract: A Discrete Component Model (DCM) is applied to study the heating and evaporation of suspended kerosene and kerosene surrogate droplets. The effects of natural convection are taken into account using the Churchill approximation, whilst the effects of heat addition from the supporting fibre are modelled using the assumption that heat supplied via the fibre is uniformly distributed within the droplet volume. The results of taking into account and ignoring the above effects are investigated. It is shown that the effect of supporting fibre can be ignored in the analysis of these droplets. In contrast, the effect of natural convection cannot be ignored. The time evolution of droplet radii predicted by the DCM, taking into account the effects of natural convection and supporting fibre, is shown to be close to experimental predictions of this parameter for gas temperatures in the range 500 °C to 700 °C. The heating and evaporation of kerosene droplets are compared with those for droplets of various kerosene surrogate fuels, including eleven surrogate fuels proposed in the literature, and two original compositions. Considering the balance between the heating and evaporation characteristics of droplets we conclude that those of the original surrogate SU1 and the modified Utah surrogate are the closest to those of kerosene droplets.